Peran Peer Support dan Occupational Identity pada Adaptabilitas Karier para Lulusan Baru - Dharmadhyaksa, Ignatius Satria; Sami'an (Universitas Airlangga, 2024)
In the era of globalization and uncertain economic conditions, the phenomenon of unemployment among fresh graduates due to lack of job competencies remains a significant challenge. This research aims to investigate the impact of peer support on career adaptability and the moderating role of various occupational identity types (achievement, moratorium, foreclosure, and diffusion). Data collection was carried out by involving 99 unemployed fresh graduates. It was analyzed using moderated multiple regression. The findings of this study indicated that peer support had a positive effect on career adaptability. Occupational identity achievement did not moderate this positive effect, while occupational identity moratorium, foreclosure, and diffusion strengthen this positive influence. The results highlight the importance of utilizing peer support effectively peer tailored to an individual's specific occupational identity to foster career development.